Oligocenska morska žaga z Brega pri Čepljah - Mikuž, Vasja (Geologija, 2004)
In paper a 168 mm long rostral tooth of a cartilaginous fish - sawfish from Breg near Čeplje is decsribed. In its proximal part the tooth is thick and broad, and in the distal part narrow, very flattened and thinned. It was foundin greenish-grey Oligocene calcareous sandstone containing some mica. This is the first recorded find of a cartilaginous fish of genus Pristis in Slovenia. The calcitic nannoplankton in the beds at Breg permits their attribution to Middle Kiscellian of the Lower Oligocene.
Keywords: fosili; oligocen; paleontologija; paleontology; ribe; Slovenia; Slovenija